(untitled) (Experimental biology, 2024)
Understanding the genetic diversity and population structure of Tulipa buhseana Boiss. is essential for its conservation and management. We investigated 282 individuals from 15 populations of T. buhseana collected in two regions (Almaty, Zhambyl) using SSR markers. Analysis revealed high genetic diversity within populations (66%) and significant differentiation among populations (34%) based on AMOVA. PCoA identified two distinct groups, consistent with the dendrogram analysis, which grouped populations into two main clusters. Bayesian analysis suggested subtle genetic structuring, supporting findings of low population differentiation by STRUCTURE. These results underscore the complex genetic dynamics of T. buhseana and emphasize the need for tailored conservation strategies to preserve its genetic diversity.